HUBUNGAN GAYA KEPEMIMPINAN TERHADAP ORGANISASI IKATAN KELUARGA BESAR KRISTEN KIMIA UNIVERSITAS NEGERI MEDAN - Agnes Secilia Simamora; Christian Salomo Pardosi, Fikri Maulana Saleh Harefa; Ririn Eriva Tampubolon, Flores Tanjung (STKIP Subang, 2026)
This study aims to examine the relationship between leadership styles implemented by leaders within an organization and the characteristics of the organization itself, as well as the resulting impact on organizational performance. Leadership styles include transformational, transactional, laissez-faire, and relational styles. Organizational characteristics include organizational culture, organizational structure, organizational climate, and organizational health. The impact on the organization is measured through organizational performance variables (productivity, innovation, effectiveness), employee or member satisfaction, organizational commitment, readiness for change, and loyalty. The research method used was qualitative, with a survey of several respondents from a student organization using a questionnaire adapted from the leadership style and organizational performance instrument. The results show that transformational and relational leadership styles have a significant positive influence on organizational performance, while laissez-faire leadership styles have a negative influence. Organizational structure and culture moderate the relationship between leadership style and performance. These findings suggest that leaders who implement a supportive, communicative, and visionary leadership style can increase organizational effectiveness.